ANALISIS PENERAPAN PENGELOLAAN KEUANGAN DESA BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2018 DI KECAMATAN MANYAR TAHUN ANGGARAN 2023 - Faizah, Aminatul; Halima, Nur (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The purpose this research is to find out and analyze the obstacles faced by villages in implementing village financial management based on Permendagri Number 20 of 2018 in Manyar District for the 2023 Fiscal Year, obstacles and solutions for village financial management based on Permendagri Number 20 of 2018 Type of Research In this research, using an approach qualitative, descriptive research type Phenomenology, testing the validity of data using triangulation. The planning, implementation, reporting and accountability processes are in accordance with Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Finance, only in the administration process there are 3 villages that are not compliant. The results of the analysis obtained as a record of fundamental changes in village financial management by researchers include, financial accounting records using the cash basis method, financial management is required to come from a device, there are changes to the codification structure and there are additional document formats for budgeting, implementation, and realization and accountability reports. everything is covered by the SISKEUDES application. The obstacles experienced by the village government are work motivation, education and training and the conscientiousness factor. The solutions are training, innovation from the Gresik Regency Community and Village Empowerment Service, motivation and monitoring approaches.